Noisy galvanic vestibular stimulation has a greater ameliorating effect on posture in unstable subjects: a feasibility study - Fujimoto, Chisato; Kinoshita, Makoto; Kamogashira, Teru; Egami, Naoya; Kawahara, Takuya; Uemura, Yukari; Yamamoto, Yoshiharu; Yamasoba, Tatsuya; Iwasaki, Shinichi (Scientific reports, 2019)
Ameliorating effect of noisy galvanic vestibular stimulation (nGVS) on posture varies among subjects. In this feasibility study, we investigated the association between original postural instability and the ameliorating effect of nGVS on posture. Data were collected in a previously published study. Thirty healthy elderly were recruited. Two nGVS sessions (30 min or 3 h) were performed in a randomised order. The optimal intensity of nGVS, the most effective intensity for improving posture, was determined before each session. Posture was measured for 30 s during and after nGVS in the eyes-closed/foam rubber condition. The velocity, envelopment area, and root mean square of the centre of pressure movement without nGVS were significantly larger in the group with an optimal intensity than those in the group without an optimal intensity. There was a significant positive correlation between these values and the long-term ameliorating effects. The ratio of the values in the eyes-closed/foam rubber condition to those in the eyes-open condition was significantly larger in the group with an optimal intensity, and had a significant correlation with the long-term ameliorating effects. The ameliorating effects are greater in subjects who were originally unstable and in those whose postural stability was relatively independent of vestibular input.